Doing Good with Technologies: Taking Responsibility for the Social Role of Emerging Technologies - Waelbers, Katinka; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
20th century technologies like cars, the Internet, and the contraceptive pill have altered our actions, changed our perceptions and influenced our moral ideas, for better and worse. Upcoming technologies are bound to fulfill their own unique social roles. How can we advance this social role so that it will support the good live and limit undesired changes? This book explores whether we can take a forward looking responsibility to optimize the social roles of technologies. In doing so, the book discusses three issues: first, it aims to understand the social role of technologies; second, it explores what it means to accept responsibility for this social role, and; third, it searches for some forward looking tools that help us to see how new technologies may influence human behavior. In a rather unique approach, this book combines the influential sociological research of Bruno Latour on the social impacts of technologies with the contemporary Aristotelianism of Alasdair MacIntyre.
Chapter 1. Introduction: responsibility for the social role of technologies -- 1.1 Designing mediating technologies -- 1.2 The main argument of this study -- Chapter 2. Mastering technologies -- 2.1 Traditional debates on the social role of technologies -- 2.2 The empirical turn in philosophy of technology -- 2.3 ANT and Responsibility -- Chapter 3. Actor-networks and taking responsibility -- 3.1 ANT and responsibility -- 3.2 Acting willingly -- 3.3 Causation and mediation -- 3.4 Foresee ability and black-boxing -- 3.5 Responsibility: three problems, three solutions -- Chapter 4. Becoming responsible for techno-social practices -- 4.1 Different styles of doing ethics -- 4.2 Intrinsic motives and practices in actor-networks -- 4.3 Embedded agency -- 4.4 Explaining forward-looking responsibility -- 4.5 An ethics for taking responsibility for the social role of technologies -- Chapter 5. Human practices in a technological contexts -- 5.1 Reinterpreting technological mediation -- 5.2 What do we perceive? Technological mediation of factual beliefs -- 5.3 What can we do? Technological mediation of options for action -- 5.4 What do we want? Technological mediation of moral beliefs -- 5.5 Again: the question of responsibility -- Chapter 6. Tools for a forward-looking responsibility -- 6.1 Part 1 of the toolbox: questions to address -- 6.2 Part 2 of the toolbox: means to answer the questions -- 6.3 Part 3 of the toolbox: evaluating the social role of technologies -- Chapter 7. Case study: Taking responsibility for future driving -- 7.1 Studying the social role of intelligent cars -- 7.2 Step 1: the aims of the technologies -- 7.3 Step 2: the involved practices -- 7.4 Step 3: common reasons of actions of the involved practices -- 7.5 Step 4: future use of the technology -- 7.6 Step 5: mediation of reasons for action -- 7.7 Evaluation -- Chapter 8. Will we accept responsibility? -- Literature.
Keywords: Philosophy (General).; Ethics; Technology -- Philosophy; Social sciences -- Philosophy; Philosophy; Philosophy of Technology; Ethics; Philosophy of the Social Sciences